ECONOMIC VALUATION OF THE MANGROVE AND PROSPECTIVE PROPERTIES CONSERVATION AREA IN THE CITY OF TARAKAN - Rani Handayani; Abd Rahman Razak; Nur Dwiana Sari Saudi (Jurnal Ekonomi, 2023)
Mangrove forests in the mangrove and proboscis monkey conservation area (KKMB) are natural resources that are closely related to the survival of the rare endemic species of Kalimantan, and also KKMB is one of the forests located in the city center which has benefits as a life support system up to a medium development of science and education, as well as having benefits in the form of services that function as nature tourism. This study aims to calculate the economic value of the mangrove and proboscis monkey conservation area in Tarakan City, North Kalimantan. The type of data used in this research is quantitative with a survey approach. The data analysis method used is the travel cost approach to determine the value of tourism objects, replacement cost to determine the abrasion-resistant value, benefit transfer to determine the value of biodiversity, and willingness to pay to determine the existence value and heritage value. Based on the results of this study indicate that the total economic value of KKMB reaches Rp. 239,482,368,922/year including a tourist object value of Rp. 318,116,633/year, the value of the abrasion barrier is Rp. 3,852,800,082/year, biodiversity value of Rp. 28,174,607/year, the mangrove existence value is Rp. 114,988,068,000/year, and the proboscis monkey's inheritance value is Rp. 120,295,209,600.